Monsters, Monsters Everywhere: Spooky TV and the Politics of Fear in Post-9/11 America. - Takacs, Stacy (Science Fiction Studies, 2009)
This essay examines the recent but short-lived spate of sf television programs focused on alien invasions of the US Homeland, including "Surface," "Invasion," and "Threshold." It argues that these programs provide tools for thinking through the Bush administration's politics of fear and its consequences for US security.